(untitled) (Journal of the College of Basic Education, 2022)
The music of the Noble Qur’an, with its unique timbre and enchanting rhythm, is a means of attracting attention on the one hand. And a challenge to what the Arabs were known for in terms of skill in saying, and skill in wording on the other hand, but The most prominent in the systems of the Qur’an is its choice of words that fit in its auditory image with the mental image, thus creating With skillful coordination, it conveys the reader to the atmosphere of the verse and its topic, whether it is an exhortation, encouragement, or intimidation. In it, Quranic studies have spread widely in our modern era due to the Holy Qur’an. It is of great importance because it is not described by pens, and even media cannot express it. And whenever we navigate in the Book of God